A Novel Application of Serum Creatinine and Cystatin C to Predict Sarcopenia in Advanced CKD - Lin, Yu-Li; Wang, Chih-Hsien; Chang, I-Chen; Hsu, Bang-Gee (Frontiers in Nutrition, 2022)
Sarcopenia is highly prevalent in patients with advanced chronic kidney disease (CKD), yet a reliable serum index has not been established. The product of serum creatinine and the estimated glomerular filtration rate based on cystatin C (Cr×eGFRcys) was recently proposed as a sarcopenia index (SI), approximately to 24-hour filtered creatinine through the glomerulus. We aimed to evaluate the diagnostic validity of the novel SI in advanced CKD. In 297 patients with non-dialysis stage 3b-5 CKD, aged 68.8 ± 12.9 years, the total skeletal muscle mass (SMM), handgrip strength (HGS), and usual gait speed were assessed. Sarcopenia was defined based on the Asian Working Group for Sarcopenia 2019 consensus update. The prevalence of sarcopenia in this cohort was 20.2%. The SI correlated moderately with SMM (r = 0.503, P < 0.001), HGS (r = 0.508, P < 0.001), and gait speed (r = 0.381, P < 0.001); the independency of the SI with three muscle metrics was confirmed after extensive adjustment. For sarcopenia prediction, the SI had acceptable discriminative powers in males (area under the receiver operating characteristic curve [AUC] 0.646, 95% confidence interval [CI] 0.569–0.718) and females (AUC 0.754, 95% CI 0.670–0.826). In males, the best cut-off was 53.9, which provided 71.1% sensitivity, 58.0% specificity, 32.9% positive predictive value (PPV), and 87.4% negative predictive value (NPV); in females, the best cut-off was 45.8, which provided 81.8% sensitivity, 62.3% specificity, 31.0% PPV, and 94.3% NPV. In conclusion, Cr×eGFRcys could be served as a surrogate marker for sarcopenia and may be helpful for sarcopenia screening in advanced CKD. Further studies are needed to expand our investigation.